Common Elements of the Bridal Gift-Giving in the Wedding Customs of the Bunjevci, the Vlach and other Balkan Peoples - Černelić, Milana (Array, 2007)
The article deals with two specific customs of the Croatian ethnic group of Bunjevci (inhabiting the region of Bačka in Vojvodina and the regions of Lika and Primorje in Croatia), which are to some extent inter-related. In the period between the marriage proposal to the actual marriage the bridegroom's relatives (often including his mother) are bringing the future bride presents primarily in food and drink, often including other gifts. The other custom is connected with the bridegroom's or his father's duty to give the bride the wedding attire or some of its parts. These two customs are sometimes practiced at the same occasion. In its specific variants both of them are also characteristic of the Vlach wedding customs, well known among other Balkan peoples as well: Greeks, Albanians, Macedonians, Bulgarians, Serbs, Montenegrins, one more dominant than the other in various regions. Traces of these elements could be followed in southern parts of the Adriatic area, some regions in Bosnia, in the region of Lika, Gorski kotar and in eastern Pannonic area in Croatia and Vojvodina. Through comparative analyses the author is aiming to reach the conclusion about the origin of these customs and their distribution in the western and northern regions of South East Europe.